1995
DOI: 10.1002/1097-0142(19951101)76:9<1491::aid-cncr2820760902>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Axillary lymph nodes and breast cancer. A review

Abstract: Background. The value of surgical staging and treatment of the axillary lymph nodes with either surgery or radiotherapy in the initial management of patients with Stage I or II invasive breast cancer is controversial. Methods. A review of retrospective and prospective clinical studies was performed to assess the risks of axillary lymph node involvement and the effectiveness and morbidity of various treatment options. Results. The risk of axillary lymph node involvement is substantial for most patients, even th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
121
0
12

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(135 citation statements)
references
References 153 publications
2
121
0
12
Order By: Relevance
“…This may be a rather short follow-up period, but in a study on outcome of axillary recurrences after ALND (Newman et al, 2000) a median time interval of 19 months for local recurrence after ALND is reported. Axillary recurrence after ALND ranges between 0 and 3% (Recht and Houlihan, 1995). We could observe no axillary recurrence in 200 patients with a median follow-up of 36 months after SLNB only.…”
Section: Discussionmentioning
confidence: 63%
“…This may be a rather short follow-up period, but in a study on outcome of axillary recurrences after ALND (Newman et al, 2000) a median time interval of 19 months for local recurrence after ALND is reported. Axillary recurrence after ALND ranges between 0 and 3% (Recht and Houlihan, 1995). We could observe no axillary recurrence in 200 patients with a median follow-up of 36 months after SLNB only.…”
Section: Discussionmentioning
confidence: 63%
“…Histopathological examination after surgical removal of at least ten axillary lymph nodes (ALN) is the standard staging procedure for determination of the axillary lymph node status (3). Today the sentinel lymph node (SLN) biopsy technique is introduced as an accurate staging procedure for small unifocal breast tumours with clinically negative axilla (4).…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Axillary lymph node dissection is therefore an important diagnostic and treatment procedure. 27 This dissection may also result in long-term upper limb morbidity. 6,8,24,27±31 Recently the sentinel node procedure was introduced to reduce the number of unnecessary axillary lymph node dissections, and thereby reducing treatment morbidity from a complete axillary lymph node dissection.…”
Section: Introductionmentioning
confidence: 99%